FACTORES PREDISPONENTES AL INICIO DE EXPERIENCIA SEXUAL EN ALUMNOS DE OBSTETRICIA UNIVERSIDAD PRIVADA DE ICA MARZO-JUNIO 2019’ - IZAGUIRRE BOLO, DEYSI EVELYN (2020)
TITLE: Predisposing factors at the beginning of sexual experience in students of Obstetrics Private University of Ica March-June 2019. Objective: To determine predisposing factors at the beginning of sexual experience in students of Obstetrics Private University of Ica March-June 2019 METHODS: This cross-sectional research, prospective observational of March-June 2019 the sample was made up of 70 adolescents and young people to apply a questionnaire and measure the knowledge that each student has; information was processed in the statistical program SPSS V 25.0. RESULTS: 63.8% are 17-21 years old, 95.7% are female, 87.1% are single and 78.6% live are their parents, 64.3% started their sex life by choice, while 47.1% did so out of love and 60% claim to receive sex education. 28.6% met their sexual partner at school and ward, 90% had vaginal sex, 87.1% started their first sexual encounter with their lover and the place where they started their first sexual relationship was in a hotel with 57.1%. 45.7% started their sex life between the ages of 15 and 17 and 52.9% did not use a condom in their first sexual activity. CONCLUSION: Due to the greatest information regarding sexuality and the spread of STIs, young people and adolescents continue to have higher risk behaviors in their sex life. KEY WORDS: Predisposing factors, onset of sexual intercourse, adolescents and young people.